2020
DOI: 10.1002/jdd.12164
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effectiveness of an online dental pharmacology course

Abstract: ObjectivesUndergraduate dentistry students in their final year often lack the knowledge and confidence required to prescribe oral health medications. Online courses could help to solve this problem through augmenting traditional teaching methods. This study assessed the effectiveness of a non‐curricular, online, clinical case‐based dental pharmacology course designed to improve medication management in senior dentistry students.Materials and methodsThis study developed and implemented an online dental pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The result of this study is consistent with those of Morales‐Pérez et al [ 29 ], Absi et al [ 32 ], and Rosenberg et al [ 33 ] regarding the effectiveness of web-based learning and web-based courses in increasing the knowledge of participants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The result of this study is consistent with those of Morales‐Pérez et al [ 29 ], Absi et al [ 32 ], and Rosenberg et al [ 33 ] regarding the effectiveness of web-based learning and web-based courses in increasing the knowledge of participants.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous studies that have investigated the effectiveness of web-based learning in enhancing participants’ knowledge and skills. This success of the course could be attributed to the well-structured presentation and content of the course, as well as the ease of use of the web-based platform (LMS-Moodle) and its flexibility in navigating the course content [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, students demonstrated significant improvement in scores from pre-workshop quiz to post-workshop quiz and all the 16 self-efficacy scores pertinent to the basic research skills. Similarly, a study conducted by Morales-Pérez et al reported significant improvement in the pre-and post- test scores of the participants after attending an online course [ 28 ]. Moreover, the outcomes of a study conducted by Soffer et al showed that students scored higher in online courses than in face to face courses [ 29 ].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, there is an agreement that the quality of instructors, assessment type, learning environment and lecture content influence overall learning for dental students. 17,[35][36][37][38][39][40][41][42] Furthermore, it is important to emphasise that supervising tutors may need additional training to ensure that they are competent in the knowledge of modern prescribing frameworks and that they understand the principles of antimicrobial stewardship and the quality use of medicines. 9,43 The current study had several strengths and limitations worth noting.…”
Section: Discussionmentioning
confidence: 99%